Novas rotas para a síntese hidrotérmica de nanoestruturas de óxidos de titânio - Mourão, Henrique Aparecido de Jesus Loures (2012)
The development of new materials has been a major focus of modern science. In order to obtain materials with desired features, studies about synthesis are necessary for a better understanding of their synthetic processes. In this light and in search for new materials in heterogeneous photocatalysis, a challenge is to understand the synthetic processes by the investigation of synthesis variables. Thus, this thesis presents the synthesis of Ti oxide nanostructures (pure or associated with Sn oxide) through the alkaline hydrothermal method. Some variables such as precursor, base concentration, temperature and time of hydrothermal treatment were studied. In the syntheses of co-precipitated Ti and Sn oxides, the formation of Sn oxide occurred only under mild alkaline conditions, since high alkalinity caused the Sn dissolution. In the evaluation of precursor type, peroxytitanium complexes (PTCs) showed excellent characteristics to obtain titanate phases in mild alkaline conditions, since the process of titanate formation from PTC occurred without the complete degradation of its initial structure. In the study about temperature and time of synthesis, the temperature of hydrothermal treatment was the most important synthetic parameter. With respect to the photocatalytic tests of synthesized materials, the crystalline phase was the most important factor. The titanates showed higher specific surface area and higher concentration of hydroxyl groups, whereas the photoactivities were lower. The low photoactivities of titanates were attributed to the majority presence of fivecoordinated titanium species (TiO5). In this study, the hexa-coordinated titanium (TiO6) was considered the main active site for photocatalytic processes.